1836 Mass. Rev. Stat., ch. 85, §24 - (:unkn) unknown (General Publisher, 1794)
Granted justices of the peace to punish, by fine of ten dollars, all assaults, batteries, and other breaches of the peace unless of a "high and aggravated nature." Including all who go armed offensively to the terror of the people, such as menaces and threatening speeches.
--
Keywords: GOING ARMED